2014
DOI: 10.1128/jb.02055-14
|View full text |Cite
|
Sign up to set email alerts
|

CcpA-Mediated Catabolite Activation of the Bacillus subtilis ilv-leu Operon and Its Negation by Either CodY- or TnrA-Mediated Negative Regulation

Abstract: The Bacillus subtilis ilv-leu operon functions in the biosynthesis of branched-chain amino acids. It undergoes catabolite activation involving a promoter-proximal cre which is mediated by the complex of CcpA and P-Ser-HPr. This activation of ilv-leu expression is negatively regulated through CodY binding to a high-affinity site in the promoter region under amino acid-rich growth conditions, and it is negatively regulated through TnrA binding to the TnrA box under nitrogen-limited growth conditions. The CcpA-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Accordingly, we constructed the supercompetent strain AW001‐5 that coexpressed xylose‐inducible comK and comS from the bpr locus (Figure ). Given that ilvBHC are expressed as part of a single operon and the regulatory elements controlling its expression are spatially defined, we chose to replace the 677 bp region upstream of the ilvB ribosome binding site (including a TnrA box [Tojo et al, ], all four CodY binding sites, a catabolite repression element and its upstream binding site [Fujita, Satomura, Tojo, & Hirooka, ], the tRNA Leu T‐box, and P ilv ‐ leu ) with the strong constitutive promoter P grac (Phan, Nguyen, & Schumann, ) in strain AW002‐5 (Figure ). In addition, we simultaneously mutated bcd to prevent the conversion of l ‐valine to 2‐ketoisovalerate in AW002‐5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we constructed the supercompetent strain AW001‐5 that coexpressed xylose‐inducible comK and comS from the bpr locus (Figure ). Given that ilvBHC are expressed as part of a single operon and the regulatory elements controlling its expression are spatially defined, we chose to replace the 677 bp region upstream of the ilvB ribosome binding site (including a TnrA box [Tojo et al, ], all four CodY binding sites, a catabolite repression element and its upstream binding site [Fujita, Satomura, Tojo, & Hirooka, ], the tRNA Leu T‐box, and P ilv ‐ leu ) with the strong constitutive promoter P grac (Phan, Nguyen, & Schumann, ) in strain AW002‐5 (Figure ). In addition, we simultaneously mutated bcd to prevent the conversion of l ‐valine to 2‐ketoisovalerate in AW002‐5.…”
Section: Resultsmentioning
confidence: 99%
“…Given that ilvBHC are expressed as part of a single operon and the regulatory elements controlling its expression are spatially defined, we chose to replace the 677 bp region upstream of the ilvB ribosome binding site (including a TnrA box [Tojo et al, 2004], all four CodY binding sites, a catabolite repression element and its upstream binding site [Fujita, Satomura, Tojo, & Hirooka, 2014], the tRNA Leu T-box, and P ilv-leu ) with the strong constitutive promoter P grac (Phan, Nguyen, & Schumann, 2012) in strain AW002-5 ( Figure 2).…”
Section: L-valine Quantificationmentioning
confidence: 99%
“…LexA represses the SOS response to DNA damage and regulates the lytic switch in the Bacillus thuriengensis temperate phage, GIL01 [19]. CcpA plays a major role in the coordinated regulation of catabolism and anabolism to ensure optimum cell propagation [53]. It also plays a key role in toxin gene expression and virulence [54].…”
Section: Detailed Analysis Of the Whole Cell Proteomementioning
confidence: 99%
“…Previous studies reported that CodY often acts additively or antagonistically with another regulator named CcpA to regulate carbon and nitrogen metabolism (21)(22)(23). CcpA can mediate repression of virulence gene expression and carbon catabolism gene expression in Gram-positive bacteria, including some Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…CcpA is a member of the LacI/GalR family of transcriptional regulators (19,20) and often works together with CodY to regulate, directly or indirectly, the expression of hundreds of genes involved in carbon and nitrogen utilization (21)(22)(23). CcpA interacts with proteins like phosphorylated HPr, which increases its affinity for certain DNA binding sites and results in repression or activation of gene transcription (20,24).…”
mentioning
confidence: 99%